Novel BaBi0.05Co0.8Nb0.15O3−δ perovskite oxide as cathode material for intermediate-temperature solid oxide fuel cells. (8th June 2015) - Meng, Xiangwei; Long, Guohui; Liu, Shouxiu; Ji, Yuan; Pang, Mingjun; Wang, Biao; Lü, Shiquan; Yang, Jinghai
Abstract A cubic perovskite oxide, BaBi0.05Co0.8Nb0.15O3−δ (BBCN) is investigated as a cathode for intermediate-temperature solid oxide fuel cells (IT-SOFCs). XRD results show that BBCN cathode is chemically compatible with the electrolyte Sm0.2Ce0.8O1.9 (SDC) at 950 °C for 5 h. The XPS results show that the Co3+/Co4+, Nb5+, Bi3+ and Ba2+ species exist in the BBCN sample. The thermal expansion coefficient (TEC) of the BBCN sample is 19.60 × 10−6 K−1 between 30 and 850 °C in air. The Rp of BBCN cathode on SDC electrolyte is 0.047, 0.077 and 0.136 Ω cm2 at 800, 750, 700 °C, respectively. A maximum power density of 507 mW cm−2 is obtained at 800 °C for single-cell with 300 μm thick SDC electrolyte and BBCN cathode. The results of this study demonstrate that BBCN can be a promising cathode material for IT-SOFCs.